PENGARUH MENGUNYAH TEBU (SACCHARUM OFFICINARUM L.) TERHADAP DEBRIS INDEKS PADA SISWA KELAS VIII SMP NEGERI 4 PINELENG - Youla Karamoy; Ni Made Yuliana; I Ketut Harapan; , Yenny Liesbeth Siahaan (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2025)
Green Betel Leaf (Piper Betle L) is a traditional medicinal plant that is closely related to dental and oral health. Betel leaves are useful for strengthening teeth, eliminating bad breath and stopping gum bleeding. Saliva also affects the pH of the mouth. A decrease in salivary pH can cause rapid demineralization of tooth elements, while an increase in salivary pH can lead to bacterial colonization that can lead to calculus formation. This research aims to determine the effect of gargling boiled green betel leaf water on saliva pH in young adults at KGPM Eben Heazer Bahu. The research location is at the KGPM Eben Heazer shoulder pastor, and the research time is in June 2024. This type of research is a quasi-experimental with a one group pretest posttest design, the sample size is 43 people, with the sample collection method using a random sampling method with inclusion criteria. Data collection was obtained from the results of measuring saliva pH using universal pH test paper, a format for examining saliva pH before and after gargling boiled green betel leaf water. Data analysis used non-parametric statistical tests with the Wilcoxon test method. The research results obtained showed that the average saliva pH value before gargling was 7.14, the saliva pH value after gargling was 7.35, with a difference in the average saliva pH value of 0.21. analysis using the Wilcoxon test shows that there is a significant effect seen from the p value = 0.002 (0.002 < 0.05). This means that there is an effect of gargling boiled green betel leaf water on the pH of saliva.